2015
DOI: 10.5935/0101-2800.20150029
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Kidney Disease in newly diagnosed patients with Human immunodeficiency virus in Ilorin, Nigeria

Abstract: CKD is very common among patients with HIV/AIDS in Ilorin. Screening and early intervention for CKD should be part of the protocols in the management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
2
9
2
1
Order By: Relevance
“…It could also disrupt many family structures in Lagos metropolis in the near future unless something positive is done to remedy the situation. There were slightly more males in the study which is different from what was reported previously [25][26][27][28]. Male predominance in the present study may not be unconnected with low socio-economic status of women and cultural practices that hinder most of them from accessing medical care in the Sub-Saharan region of Africa [29].…”
Section: Discussioncontrasting
confidence: 96%
“…It could also disrupt many family structures in Lagos metropolis in the near future unless something positive is done to remedy the situation. There were slightly more males in the study which is different from what was reported previously [25][26][27][28]. Male predominance in the present study may not be unconnected with low socio-economic status of women and cultural practices that hinder most of them from accessing medical care in the Sub-Saharan region of Africa [29].…”
Section: Discussioncontrasting
confidence: 96%
“…The prevalence of CKD in our study was 11.7% among HAART-treated individuals, using the Modification of Diet in Renal Disease method of estimation, which is in line with the prevalence of 9.9% in a study conducted in Ghana20 but lower than that in studies conducted in Nigeria and Burundi with CKD prevalence of 47.6% and 45.7% among HIV patients, respectively 24,25…”
Section: Discussionsupporting
confidence: 88%
“…The high prevalence of renal dysfunction (24.7%) from this study could be attributed to the strict criteria used in this study, and lower threshold in screening for renal dysfunction enables early detection of the patients and hence room for providing earlier interventions. Higher magnitudes (53–76%) of renal dysfunction were reported among ART-naive patients compared to our findings [ 5 , 11 ]. Most of our participants had good viral suppression, indicating possibly ART medications may be protective of renal dysfunctions.…”
Section: Discussioncontrasting
confidence: 74%